A Cognitive Semiotic Analysis of Visual Poetry in Iain S. Thomas' ''Every Word You Cannot Say'' (Journal of the College of Basic Education, 2026)
This study aims to examine the making of multimodal metaphors in visual poetry through a cognitive linguistic approach. This study uses the multimodal metaphor framework of Forceville (1996) in analysing two visual poems from Every Word You Cannot Say by Iain S. Thomas. Although multimodality is gaining more and more recognition in discourse analysis, there is still limited research that examines how verbal and visual modes combine as a semiotic system in metaphor construction in visual poetry. The study aims to fill in this gap by examining how verbal and visual modes combine in metaphor construction and how they engage the reader cognitively. The research will employ a qualitative method of analysis, which will be based on the interpretive analysis of the verbal and visual components of the target poems. The process of analysis will include the identification of metaphorical expressions, their domains of source and target, and the process of mapping these expressions across the two modes. The results indicate that the use of language, images, and typography in Thomas’ visual poetry helps to create meaning and engage the reader culturally and bodily.